Rate Region of the One-Help-Two Quadratic Gaussian Source-Coding Problem with Markovity - Bilgen, Omer; Wagner, Aaron B. (IEEE transactions on information theory, 2023)
We study the quadratic Gaussian one-help-two source-coding problem with Markovity, in which three encoders separately encode the components of a memoryless vector-Gaussian source that form a Markov chain and the central decoder aims to reproduce the first and the second components in the chain subject to individual mean-squared distortion constraints. We determine the rate region under a high-resolution assumption for the middle source.